2018
DOI: 10.13057/biodiv/d190108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bacterial endophytes from potato roots and tubers on potato cyst nematode (Globodera rostochiensis)

Abstract: Istifadah N, Pratama N, Taqwim S, Sunarto T. 2018. Effects of bacterial endophytes from potato roots and tubers on potato cyst nematode (Globodera rostochiensis). Biodiversitas 19: 47-51. Bacterial endophytes are bacteria that inhabit plant tissues without causing any diseases. The endophytes existence may have negative, neutral, or positive effects on the host plants. This paper discusses the effects of bacterial endophytes isolated from potato roots and tubers on potato growth and their abilities to suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…and P. pseudoalcaligens effectively suppressed all kinds of G. rostochiensis propagules. This result confirmed previous studies that also found these microbes significantly reduced the numbers of second stage juveniles and cysts of G. rostochiensis in the soil (Istifadah et al, 2017;Istifadah et al, 2018). In the in vitro test, the culture filtrate of P. pseudoalcaligens also caused high mortality (97.9%) of second-stage of the nematode.…”
Section: The Effects Of the Microbial Enrichment Of The Organic Materials On The Nematode Suppressionsupporting
confidence: 91%
See 2 more Smart Citations
“…and P. pseudoalcaligens effectively suppressed all kinds of G. rostochiensis propagules. This result confirmed previous studies that also found these microbes significantly reduced the numbers of second stage juveniles and cysts of G. rostochiensis in the soil (Istifadah et al, 2017;Istifadah et al, 2018). In the in vitro test, the culture filtrate of P. pseudoalcaligens also caused high mortality (97.9%) of second-stage of the nematode.…”
Section: The Effects Of the Microbial Enrichment Of The Organic Materials On The Nematode Suppressionsupporting
confidence: 91%
“…The filtrate of the bacteria caused lysis of the juvenile cell walls, indicating the presence of cell wall degrading enzyme (Istifadah et al 2018).…”
Section: The Effects Of the Microbial Enrichment Of The Organic Materials On The Nematode Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated significant control of M. incognita in potato from R. etli G12 application with 34% fewer galls than in control [ 64 ]. Bacillus carotarum , B. cereus , and Pseudomonas pseudoalcaligenes isolated from the roots and tubers of potato caused ≥80% mortality of Globodera rostochiensis J2s in vitro but did not limit the egg-hatch [ 66 ].…”
Section: Endophytes As Bionematicidesmentioning
confidence: 99%
“…Contrary to the expectation, E. ludwigii BUMS resulted in average potato shoot length and weight that were less than those of the un-inoculated control by 3.94% and 5.94%, respectively. The failure of rhizobacterial inocula to produce the desired results during in planta investigations is probably due to the inabilities to establish themselves in the rhizosphere (Istifadah et al 2018).…”
Section: Effects Of the Rhizobacterial Treatments On Growth And Yield Of Potted Potatoesmentioning
confidence: 99%